Ethnobotany and agrobiodiversity: valuation of plants in the homegardens of Southwestern Uganda - Whitney, Cory W.; Bahati, J.; Gebauer, J. (Society of Ethnobiology, 2018)
Homegardens are species-rich agroforestry systems with a high diversity of associated traditional knowledge. These systems are an important part of food security for rural marginalized poor around the world, particularly in the humid tropics. Despite the high diversity and cultural importance, little is known about the livelihood-relevant plant diversity contained in the homegardens of southwestern Uganda. Here we employ the quantitative ethnobotany indices use reports (UR) and the cultural importance index (CI) to describe the importance of plants and plant types in the region’s homegardens. Data is based on inventories of 102 homegardens in the Greater Bushenyi from 2014 and reveals 225 useful plant species in 14 different use categories with 3,961 UR, 54% for food, 15% for economic uses, and 11% for medicine. The findings highlight the importance of homegarden plants for subsistence farming households and indicate that they are important places for conservation of botanical agrobiodiversity that should be considered part of the conservation movement in Uganda. Efforts to conserve both botanical and food system diversity in the extremely rich but rapidly deteriorating regional socio-cultural and ecological systems should consider homegardens for their role in conservation of plants and preservation of traditional knowledge.